Physical Anthropology : An introduction - Ciochon , Russell L.; Ciochon, Russell L (Australia : Wadsworth, 2012)
Physical Anthropology: An Introduction, International Edition continues to present the most up-to-date and balanced, comprehensive introduction to the field, combining an engaging writing style and compelling visual content to bring the study of physical anthropology to life for today's students. With a focus on the big picture of human evolution, the text helps students master the basic principles of the subject and arrive at an understanding of the human species and its place in the biological world. This book continues to keep pace with changes in the field by including thorough coverage of cutting-edge advances in molecular biology and genomics, primatology, key fossil discoveries, and modern human biology. A new Conclusion: Why it Matters, drives home the importance of understanding human evolution and the incredible impact our species has had, and will continue to have, on the environment and all life forms on this planet.
Includes Glossary 543-551p.; Bibliography 552-573p.; Pholt credits 574-576p.
Keywords: Contemporary human evolution; Hominin evolution